Staphylococcus aureus causes aberrant epidermal lipid composition and skin barrier dysfunction. Issue 5 (19th January 2023) - Kim, Jihyun; Kim, Byung Eui; Berdyshev, Evgeny; Bronova, Irina; Bin, Lianghua; Bae, Jaewoong; Kim, Seokjin; Kim, Hye‐Young; Lee, Un Ha; Kim, Myoung Shin; Kim, Hyunmi; Lee, Jinyoung; et al.
Abstract: Background: Staphylococcus ( S ) aureus colonization is known to cause skin barrier disruption in atopic dermatitis (AD) patients. However, it has not been studied how S . aureus induces aberrant epidermal lipid composition and skin barrier dysfunction. Methods: Skin tape strips (STS) and swabs were obtained from 24 children with AD (6.0 ± 4.4 years) and 16 healthy children (7.0 ± 4.5 years). Lipidomic analysis of STS samples was performed by mass spectrometry. Skin levels of methicillin‐sensitive and methicillin‐resistant S . aureus (MSSA and MRSA) were evaluated. The effects of MSSA and MRSA were evaluated in primary human keratinocytes (HEKs) and organotypic skin cultures. Results: AD and organotypic skin colonized with MRSA significantly increased the proportion of lipid species with nonhydroxy fatty acid sphingosine ceramide with palmitic acid ([N‐16:0 NS‐CER], sphingomyelins [16:0–18:0 SM]), and lysophosphatidylcholines [16:0–18:0 LPC], but significantly reduced the proportion of corresponding very long‐chain fatty acids (VLCFAs) species (C22–28) compared to the skin without S. aureus colonization. Significantly increased transepidermal water loss (TEWL) was found in MRSA‐colonized AD skin. S . aureus indirectly through interleukin (IL)‐1β, tumor necrosis factor (TNF)‐α, IL‐6, and IL‐33 inhibited expression of fatty acid elongase enzymes (ELOVL3 and ELOVL4) in HEKs. ELOVL inhibition was more pronounced by MRSA and resulted in TEWL increase in organotypic skin. Conclusion: Aberrant skin lipid profiles and barrier dysfunction are associated with S. aureus colonization in AD patients. These effects are attributed to the inhibition of ELOVLs by S. aureus ‐induced IL‐1β, TNF‐α, IL‐6, and IL‐33 seen in keratinocyte models and are more prominent in MRSA than MSSA. Abstract : MRSA induces a broad range of cytokines, while MSSA induces IL‐1β and TNF‐α. Staphylococcus aureus ‐induced IL‐1β, TNF‐α, and IL‐6 inhibit ELOVL3, resulting in accumulation of lipids with C14‐C18 FAs, while MRSA‐induced IL‐33 inhibits both ELOVL3 and ELOVL4, concomitantly increasing lipids with C14‐C18 FAs and decreasing lipids with FAs ≥ 22. S . aureus ‐mediated aberrant lipid profiles cause increased TEWL and skin barrier dysfunction.Abbreviations: 3D skin, organotypic skin; ELOVL, fatty acid elongase; FA, fatty acid; IL, interleukin; MRSA, methicillin‐resistant Staphylococcus aureus ; MSSA, methicillin‐sensitive Staphylococcus aureus ; SA, Staphylococcus aureus; TEWL, transepidermal water loss; TNF, tissue necrosis factor